Employee Job Satisfaction in IT Industry in Bangalore: An Empirical Study - Fernandes, Ms. Sharmila; Sudarkodi, Dr. P. (The journal of contemporary issues in business and government, 2022)
This paper empirically examined the impact of employee job satisfaction on organizational performance in large and medium scale manufacturing industries. It notes that Employee job satisfaction is vital for improved organizational performances. The paper tells that an employee with a high level of job satisfaction holds positive attitudes towards his job. On the contrary, an employee who is dissatisfied with his job holds negative attitudes about the job. The aim of this study is to analyze the impact of employees job satisfaction on organizational performance among the employees working in IT industry in Bangalore and also to explore the link between job satisfaction and organizational performance and to determine if there is an empirically provable relationship between these two variables, and the direction and the intensity of this relationship. Empirical research was conducted on a research sample of five software companies (TCS, Wipro, Infosys, Accenture and IBM) with 155 employees surveyed. The results of this study show the existence of a clear link between employees’ job satisfaction and organizational performance in both directions, but with pretty weak intensity. Study concluded that job satisfaction determines organizational performance, rather than organizational performance determining job satisfaction.